Magnetotellurics study of Atambua area, West Timor, Indonesia - Wijanarko, Edy; Arisbaya, Ilham; Sumintadireja, Prihadi; Warsa,; Grandis, Hendra (Vietnam Journal of Earth Sciences, 2022)
Timor Island, located in the eastern Indonesian archipelago, has a complex tectonic evolution causing complex geological structures. Many hypothetical tectonic models are proposed mainly based on regional geological and geophysical data. Available geophysical data to support geological study at a more detailed scale are still very limited. Therefore, this study aimed to map the sub-regional subsurface geology in Atambua, West Timor, and its surroundings by using the magnetotelluric (MT) method. The estimated geo-electrical strike direction from the phase tensor analysis confirmed the regional Southwest - Northeast general structural orientation. The dimensionality analysis also showed the validity for 2D approximation in that direction. The subsurface resistivity models from 2D inversion of the MT data at representative lines perpendicular to the regional structural direction delineate the primary sequences and their boundaries from their resistivities. They are, from top to bottom, Viqueque and Bobonaro sequences, Kolbano sequence, Kekneno sequence, and the basement dominated by rocks with Australian affinity. These main rock formations represent the regional sedimentary depositional fill resulting from the major tectonic events on Timor Island.